Tokenizing assets with dividend payouts—a legally compliant and flexible design - Efim Zhitomirskiy; Stefan Schmid; Martin Walther (Digital Finance, 2023)
The tokenization of financial assets using blockchain technology is a transformative process that allows for the fractionalization of ownership, thereby creating more accessible investment opportunities compared to traditional financial assets. Recent research has shown that token offerings are subject to moral hazard and fraud. In response to these challenges, we propose a novel token design that is compliant with the legal framework of Switzerland. Our design is characterized by its flexibility and can represent any yield or dividend-bearing asset, such as stocks, bonds, or rental income from real estate. Further enhancing its compatibility, the token conforms to the Ethereum ERC-20 standard, enabling seamless integration with existing decentralized finance solutions. Another contribution of our token design is its innovative approach to dividend distribution. Unlike traditional models that distribute dividends based on ownership at the time of payment, our token design distributes dividends based on holding times. This distinctive approach promotes smoother asset prices between dividend payouts by eliminating the need for compensation payments. Our token prototype represents a potential starting point for future research on leveraging the opportunities of decentralized finance.
Keywords: G18; G23; G32; K22; M13; O33; 330; Blockchain; Crowdsourcing; Dividend distribution; Decentralized finance; Security token; Tokenization